Redo MIDCAB in a Septuagenarian in our Setting, Fantasy or Fact? - A Case Report (Bangladesh Heart Journal, 2021)
Worldwide growth in elderly population has led to an upsurge in the number of septuagenarian (>70 years of age) patients requiring surgical treatment for coronary artery disease. Elective coronary artery bypass grafting (CABG) in the older patients are associated with acceptable risks of adverse events and should be undertaken for appropriate indications without unnecessary hesitation. Redo coronary surgeries carries one of the highest mortality rates amongst redo cardiac surgeries, both separately or in combination with other pathologies. As a result, minimally-invasive direct coronary artery bypass (MIDCAB), was preferred to avoid the complications of re-sternotomy. We hereby present a case report of a septuagenarian patient with post CABG (2014) unstable angina with old myocardial infarction (extensive anterior) who was treated successfully, by us and to our best knowledge in the published articles this is probably the first time, a re-do MIDCAB technique has been implemented in our country.Bangladesh Heart Journal 2021; 36(2): 145-150